Compound heterozygosity for a hemizygous rare missense variant (rs141999351) and a large CNV deletion affecting the FSTL5 gene in a patient with schizophrenia. (December 2017) - Gardella, Rita; Sacchetti, Emilio; Legati, Andrea; Magri, Chiara; Traversa, Michele; Gennarelli, Massimo
Highlights: We identified a potential damaging variant in the FSTL5 gene of a schizophrenia patient. The patient was also a carrier of a CNV deleting almost the whole FSTL5 gene. Our findings are consistent with the double-hit hypothesis of schizophrenia. FSTL5 may be a candidate gene in schizophrenia.